"We need to slowly break down this barrier": understanding the barriers and facilitators that Afro-Caribbean undergraduates perceive towards accessing mental health services in the UK. Issue 1 (5th February 2020) - Sancho, Tamara Nadine; Larkin, Michael
Abstract : Purpose: Undergraduates are highly susceptible to the development of mental health difficulties. Afro-Caribbean students are particularly vulnerable to the pressures of university yet are less likely than other ethnic groups to receive early intervention. This paper aims to understand the barriers and facilitators that Afro-Caribbean undergraduates perceive towards accessing mental health services in the UK. Design/methodology/approach: Critical Incident Technique was used as the qualitative method because it explores the critical factors that contribute to or detract from a specific experience. Seventeen Afro-Caribbean undergraduates participated in five focus groups. This involved engaging in a novel psychosocial activity that incorporated vignettes to encourage the identification of barriers and facilitators to service access. The data were analysed thematically to generate categories of critical incidents and wish-list items. Findings: Analysis revealed rich data from a sub-group rarely researched within UK literature. Fifteen barriers, eleven facilitators and five wish-list items were identified. The importance of mental health literacy, social networks, cultural sensitivity and concerns surrounding services underpinned many categories. Originality/value: Findings provide a new perspective on barriers reported in previous literature. Novel facilitators were highlighted where, although psychological and sociocultural factors were deemed valuable, structural changes were most desired. Recommended changes illustrate innovative interventions that could make services accessible for young adult Afro-Caribbean populations. Future research should explore the barriers and facilitators identified by Afro-Caribbean undergraduates across various universities who have successfully accessed and engaged with services. This could provide a holistic perspective on viable facilitators enabling access despite the presence of barriers.